The effect of clinical supervision model on nursing interns medication safety competence and knowledge: A clinical trial - Amir Shahzeydi; Sedigheh Farzi; Mohammad Javad Tarrahi; Sima Babaei (Nursing and Midwifery Studies, 2023)
Background: Medication errors are the most serious and common events threatening patient safety. Nursing interns make medication errors due to inexperience and inadequate supervision.Objectives: This study aimed to examine the effects of the clinical supervision model (CSM) on medication safety competency and knowledge of nursing interns.Methods: This clinical trial was conducted in 2022 on 70 nursing interns. Data were collected using the Medication Safety Critical Element Checklist, the Medication Safety Knowledge Assessment, and the Manchester Clinical Supervision Scale. The CSM and routine supervision were conducted in six sessions for the intervention and control groups, respectively. Data were analyzed using the independent t-test, paired t-test, chi-square test, and repeated measures analysis of variance.Results: Between-group analysis showed that the difference between medication safety competence and knowledge scores in the control and intervention groups was not significant at baseline (P>0.05). Within-group analysis showed that medication safety scores in the intervention group increased significantly over time (P<0.001), in contrast to the control group (P=0.137). Within-group analysis revealed significant changes in medication safety knowledge scores in both the control and intervention groups before and after the intervention (P<0.05). However, between-group analysis showed that the increase was higher in the intervention group than in the control group (P<0.001). The mean Manchester Scale score for the intervention group was 127.2, indicating the significant effect of the CSM.Conclusion: Implementation of the CSM improves the competence and knowledge of nursing interns in the area of medication safety.